Analisis Kebutuhan Bahan Ajar Geometri Berbantuan Aplikasi Komputer - Fertilia Ikashaum; Kartika Sari Dewi; Lena Wahyuni (Jurnal Komputasi, 2019)
This research aimed to find out the need for modules aided by computer applications in the geometry course at IAIN Metro. This research is a descriptive exploratory study. The method used in the form of a questionnaire which completed with interviews to get more in-depth results. Data obtained from the percentage of the results of the total number of responses for all respondents then analyzed descriptively qualitatively. The conclusion of this study is that it needs to be developed teaching materials in the form of modules aided by computer applications in geometry courses.